Benefits of Baculovirus Use in IPM Strategies for Open Field and Protected Vegetables - Landwehr, Anna (Frontiers in Sustainable Food Systems, 2021)
Widespread use of synthetic chemical insecticides causes growing concern regarding the risks to human health and negative impacts on the environment. At the same time, many insects have become resistant towards synthetic chemical insecticides. Baculoviruses bring many benefits and allow reduced use of synthetic insecticides when included in integrated pest management (IPM). They are specific to their target pest and thus do not have any negative effects on plants, mammals, and non-target insects including natural enemies and pollinators. In addition, their unique mode of action makes them suitable for resistance management. We provide examples of how baculoviruses can be applied in IPM strategies for open field and protected vegetable crops. In field trials, baculovirus products were applied in rotations and tankmixes with chlorantraniliprole, Bacillus thuringiensis products and spinosad and provided promising control of target pests. The conducted trials in open field and protected vegetables show that baculoviruses can offer an effective solution to control pests in open field and protected vegetable production. Including baculoviruses gave results as good as other application strategies tested while conferring important benefits in reducing residues and improving the resistance management strategy.